Cooperative transmission scheme for multi-hop underwater acoustic sensor networks. (1st January 2015) - Tan, Do Duy; Kim, Dong-Seong
In this paper, we propose a cooperative transmission scheme for multi-hop underwater (UW) acoustic sensor networks to enhance network performance. Relay nodes are employed as virtual antennas to achieve diversity gains. Based on the distinct characteristics of the UW channel, such as high transmission loss, propagation delay and ambient noises, this paper presents a distributed cooperative scheme, including networking protocol and cooperative transmission at the physical layer, to enhance reliability by providing diversity gains through intermediate relay nodes. The destinations and potential relays are selected from a set of neighbour nodes that consider the distance cost and local measurement of the channel conditions into calculation. The simulation and numerical results show that the proposed scheme outperforms the traditional direct transmission schemes in terms of average energy consumption, packet delivery ratio and end-to-end delay.